Color images of infrared stimulated luminescence (IRSL) from granite slices exposed to radiations - Hashimoto, T.; Usuda, H.; Yawata, T. (Ancient TL, 2002)
Color luminescence images, associated with stimulation by infrared light, were obtained from some granite slices after X-ray irradiation of 200 Gy. The infrared stimulated luminescence color images (abbreviated to IRSL-CI) showed two colors, separable into intense yellow and blue portions. The former was assigned to be originated from a plagioclase feldspar constituent and the latter to potassium feldspar one. Quartz parts scarcely gave distinct IRSL-pattern. From spectrometry of the IRSL, two main emission peaks, consisting of 550 nm (yellow) and 580 nm (orange), were revealed besides moderate emission in wavelengths shorter than 450 nm (blue). Unexpectedly, reddish IRSL was observed in white mineral, probably feldspar of one granite. This IRSL-CI method can be useful for the examination of feldspar purity as well as for the filter selection of IRSL-dating.